If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 4(x + 6) + -7 Reorder the terms: y = 4(6 + x) + -7 y = (6 * 4 + x * 4) + -7 y = (24 + 4x) + -7 Reorder the terms: y = 24 + -7 + 4x Combine like terms: 24 + -7 = 17 y = 17 + 4x Solving y = 17 + 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 17 + 4x
| x-5/9=8/9 | | 5+4x+5+48= | | -3(t-4)+9t=8t-6 | | 60y^2+3y-36=0 | | x^2=14-7x | | 5(x-8)+26= | | 5x-4(4x-1)=2 | | -6x-142=2x+98 | | 5x+45+9x=180 | | 17=64-n | | i7n/9-62=5n/9-49 | | 31x=56 | | Y/3-4=-2 | | B/5-2=2 | | 4+-6+9=x | | .10x+12y=2990 | | a/4-b/3=5/12 | | -2+5n+3n^2=0 | | 10=30/z | | 9p-19=5(p-2)-2(7-2p) | | 5v-5v+v=16 | | Y=-4(6)-10 | | (14-2x)+40=180 | | -2x-10=-2x-10 | | x-10y=13 | | 1=k/10-1 | | x^2-14x-40= | | (14-2x)+40=90 | | 12x+6y= | | 2(-6p+7)+4(p+3)= | | 3x^2-20x+25= | | 11d-4d-3d+d-4d=12 |